Mengoptimalkan Manajemen Persediaan Melalui Teknologi Rantai Pasokan - Octaviany, Tia; Gunawan, Ahmad (CV. ITTC INDONESIA, 2023)
Effective inventory management is very important for companies to meet consumer demand on time and at low cost. An approach that can be used to optimize inventory management is to implement supply chain technology. This article discusses the concepts and benefits of supply chain technology as well as implementation steps to achieve supply chain optimization. Supply chain technology involves the efficient coordination of the various functions and entities involved in the supply chain, such as suppliers, manufacturers, distributors, and customers. Implementing supply chain technology can provide a number of significant benefits for companies, such as increasing operational efficiency, reducing costs, increasing customer satisfaction, and increasing supply reliability. Proper implementation steps can help companies optimize inventory management and achieve competitive advantage.